Akulturasi Budaya Masyarakat Etnis India-Minang di Kampung Pondok Kota Padang - Ahdal Walid (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This study discusses pluralism in the scope of cultural diversity in the Pondok village of Padang city. This study aims, first, to explain the efforts of the Indian ethnic community to be accepted in the environment, and second, to describe the Geniun culture of the Indian ethnic group that is accepted by the local culture. This study uses a qualitative descriptive research method that focuses on the data that is described until it becomes complete data in completing this study. The results of this study found that the original culture brought from India can be well accepted by the local community, this can be seen from the involvement of people outside the Indian ethnic group in the celebration procession called the Serak Gulo event.